1978
DOI: 10.1007/bf00235566
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of subjective pain experience with cerebral evoked responses to noxious thermal stimulations

Abstract: The relationships between different parameters of the evoked cerebral response to noxious thermal stimulation, stimulus intensity, and subjective pain were investigated in seven normal human volunteers. The evoked response was characterized by late events: a small negative peak at 164--180 ms, followed by a high amplitude positive peak at 372--391 ms. The only correlation found in this study was between the amplitude of the positive component and the qualitative and quantitative aspects of the verbal report of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(45 citation statements)
references
References 8 publications
5
39
1
Order By: Relevance
“…4). This indicates that the N2 and P2 waves reflect cortical processes related, directly or indirectly, to the conscious detection of nociceptive input, and agrees with the early findings by Carmon et al (1978), showing that the magnitude of the laser-evoked N2 and P2 waves correlates better with the intensity of perception than with the intensity of the nociceptive stimulus per se. It should be noted that unperceived stimuli were still able to elicit N2 and P2 waves, albeit of much reduced magnitude (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…4). This indicates that the N2 and P2 waves reflect cortical processes related, directly or indirectly, to the conscious detection of nociceptive input, and agrees with the early findings by Carmon et al (1978), showing that the magnitude of the laser-evoked N2 and P2 waves correlates better with the intensity of perception than with the intensity of the nociceptive stimulus per se. It should be noted that unperceived stimuli were still able to elicit N2 and P2 waves, albeit of much reduced magnitude (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…This was indicated by the decrease of CSSERP amplitude P2 [16,27,36]. It has previously been demonstrated that event-related potentials represent an objective tool for assessment of pain and analgesic effects [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Thus, our data indicate the presence of analgesic effects of both flurbiprofen enantiomers.…”
Section: Discussionsupporting
confidence: 61%
“…Using a variety of stimulation techniques, ERPs have been shown to correlate well with the ratings of pain intensity [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Furthermore, event-related potentials have been used to assess the analgesic effects of numerous drugs [15,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In the last ten years several studies have demonstrated the possibility of eliciting evoked potentials to different types of natural stimulation: mechanical defonnation of the skin of the finger (Pratt el al., l 979a, b, c, 1980(Pratt el al., l 979a, b, c, , 1981Ishiko et al, 1980;Pratt and Starr, 1981), flexion or extension of the ankle joint and thermal stimulation (Carmon et al, 1978). These alternative methods have the advantage of (1) providing information about the function of the receptors and terminal nerve fibres which electrical stimulation of nerve trunks bypasses and (2) activating reJatively specific types of neural elements and central pathways.…”
Section: Introductionmentioning
confidence: 99%